Examining Teacher Perspective on the Teacher Professional Program to Enhance Instructional Practices in the School Environment - Alfatha, Beniqno Rizki; Suryanto, Jati; AlQuds, Atharidha Nafistiansyah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Education is a crucial element in Indonesia. Teachers have an important part in enhancing the quality of education in Indonesia. The significant demand for professional teachers is essential for enhancing the learning process, hence positively influencing the quality of education in Indonesia. The Pre-service teacher professional program intends to enhance the professionalism of teachers, hence raising the quality and standards of education in Indonesia.This study aims to examine teacher perception towards Pre-Service Teacher Profession Program in enhancing pedagogical learning within classroom. It explores how Pre-Service Teacher Professional Education will contribute to improving instructional practice for teachers who have attended the program within the school setting.. The research employs a qualitative descriptive design, utilizing in-depth interviews with one elementary teacher and five teachers from vocational high school to gather insights on their experiences and perspective regarding Teacher Profession Program. The results of this study showed that after experiencing Teacher Professional Program, The participants believe that Teacher Professional Program will 1) Increase teacher competency, 2) Improve teachers motivation and self-confidence, 3) Give various learning strategies, 4) Increase the teacher professionalism, and 5) Integrate classroom activities with technology. These are the result of teacher perspective after conducting pre-service teacher professional program. It appears that Teacher Professional Program will give several advantage to some teachers and get new insight for teaching in the classroom. Therefore, this study is beneficial for those who will become future teacher and still hesitate for taking Teacher Professional Program.